Anti- and Protumorigenic Effects of PPARγ in Lung Cancer Progression: A Double-Edged Sword. (12th August 2012) - Li, Howard; Weiser-Evans, Mary C. M.; Nemenoff, Raphael
Abstract : Peroxisome proliferator-activated receptor- γ (PPAR γ ) is a member of the nuclear receptor superfamily of ligand-activated transcription factors that plays an important role in the control of gene expression linked to a variety of physiological processes, including cancer. Ligands for PPAR γ include naturally occurring fatty acids and the thiazolidinedione class of antidiabetic drugs. Activation of PPAR γ in a variety of cancer cells leads to inhibition of growth, decreased invasiveness, reduced production of proinflammatory cytokines, and promotion of a more differentiated phenotype. However, systemic activation of PPAR γ has been reported to be protumorigenic in some in vitro systems and in vivo models. Here, we review the available data that implicate PPAR γ in lung carcinogenesis and highlight the challenges of targeting PPAR γ in lung cancer treatments.